Theories and principles of good governance in the Shariah and the civil law: its constitutional framework in the United States and Egypt - Mokhtar, Khairil Azmin; A-Omran, Nayel Musa Shaker (LexisNexis, 2011)
Some countries have been criticised in a number of ways for their perceived lack of healthy governance, political injustice and the undermocratic system of the government. This paper is an attempt to discover theories and principles of good governance in the Shariah and civil law. It is also an attempt to cover some of the important principles which are relevant to a discourse on Islamic politics and how these principles can be used to establish good governance in Islamic states. Moreover, it is an attempt to answer the question on whether or not the Islamic legal system has known theories and principles of good governance. Thia paper also attempts to observe the incorporation of theories and principles of good governance in the Egyptian and American constitutional framework.